Boundary Spanners' Identification, Intergroup Contact, and Effective Intergroup Relations - Richter, Andreas W.; West, Michael A.; van Dick, Rolf; Dawson, Jeremy F. (Academy of Management Journal, 2006)
We examined the relationship between group boundary spanners' work group identification and effective (i. E., harmonious and productive) intergroup relations in 53 work groups in five health care organizations. The data suggest this relationship was moderated by boundary spanners' levels of organizational identification, thus supporting a dual identity model. Limited support was found for the moderating effect of intergroup contact. Finally, if boundary spanners displayed frequent intergroup contact and identified highly with their organization, group identification was most strongly related to effective intergroup relations.